(untitled) (Acta Polytechnica CTU Proceedings, 2018)
Knowledge of the complex deformation behavior in the anisotropic materials is one of essential issues in materials science and it is crucial for the applications of a given material. In this study, mechanical response of Fe3(wt.%)Si single crystal to nanoindentation with spherical indenter was investigated. Hardness and indentation Young´s modulus were determined experimentally and by finite element modelling. Observed pop-in phenomenon, shape of the residual imprints and origin of the slip lines were explained on the basis of resolved shear stress computed by finite element model.